Effect of Inclusions on Fatigue Strength of Heat Treated Components - Linhart, Vaclav; Mikulova, Dagmar; Cerny, Ivo (Communications - Scientific letters of the University of Zilina, 2010)
Inclusions significantly affect fatigue properties of quenched and tempered parts. Data about inclusions importance in fatigue crack initiation process were acquired within the framework of a systematical fatigue test programme carried out to verify fatigue properties of CrNiMo(V) steels quenched and tempered to 800 1000 MPa strength. A valuable set of fatigue failures from the high lifetime area was acquired. Microfractographical analysis of these failures enabled to evaluate critically the influence of inclusions, their dimensions, character and morphology on the initiation and propagation of the fatigue cracks in the area of fatigue strength. Comparison of inclusions size “a” according to Murakami with size determined experimentally was made. Limiting influence of small single inclusions in the structure was shown. Initiation of secondary fatigue cracks on inclusions outside of the fracture initiation area was observed. Danger of the fracture initiation after very high lifetime was confirmed.